Identifying Etiologically Distinct Sub‐Types of Cancer: A Demonstration Project Involving Breast Cancer. (13th May 2015) - Begg, Colin B.; Orlow, Irene; Zabor, Emily C.; Arora, Arshi; Sharma, Ajay; Seshan, Venkatraman E.; Bernstein, Jonine L.
<x xml:space="preserve">Abstract</x> This is an exploratory study of tumor profiling using an expression panel of 196 genes implicated in breast cancer to determine which genes best distinguish cases on the basis of etiology. Two distinct novel study designs are employed, but both support the premise that estrogen receptor expression is a dominant factor that distinguishes etiologic subtypes. <boxed-text content-type="graphic" id="cam4456-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>